Fluoride releasing in polymer blends of poly(ethylene oxide) and poly(methyl methacrylate) - Wang, Tianxiao; Li, Menghong; Gu, Ziyan; Qu, Chengjuan; Segervald, Jonas; Salh, Roushdey; Wågberg, Thomas; Wang, Jia; Kou, Wen (Frontiers in Chemistry, 2024)
Introduction: Polymethyl methacrylate is a polymer commonly used in clinical dentistry, including denture bases, occlusal splints and orthodontic retainers. Methods: To augment the polymethyl methacrylate-based dental appliances in counteracting dental caries, we designed a polymer blend film composed of polymethyl methacrylate and polyethylene oxide by solution casting and added sodium fluoride. Results: Polyethylene oxide facilitated the dispersion of sodium fluoride, decreased the surface average roughness, and positively influenced the hydrophilicity of the films. The blend film made of polymethyl methacrylate, polyethylene oxide and NaF with a mass ratio of 10: 1: 0.3 showed sustained release of fluoride ions and acceptable cytotoxicity. Antibacterial activity of all the films to Streptococcus mutans was negligible. Discussion: This study demonstrated that the polymer blends of polyethylene oxide and polymethyl methacrylate could realize the relatively steady release of fluoride ions with high biocompatibility. This strategy has promising potential to endow dental appliances with anti-cariogenicity.